2017
DOI: 10.1016/j.jfoodeng.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in emulsion stability of dairy beverages treated by high pressure homogenization: A pilot-scale feasibility study

Abstract: The impact of high pressure homogenization (HPH) on physical characteristics and emulsion stability of nutritional formulations were evaluated on a pilot scale HPH unit. Two products of industrial interest were used for these experiments. Manufactured formulations were analyzed using material characterization methods as particle size distribution, microscopy and dynamic mechanical spectra, compared to a control formula manufactured with conventional homogenization and heat treatments. Dynamic rheological measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…As compared to heat of compression (3 °C/100 MPa for water at 25 °C initial temperature), the heat generated during homogenization is much higher (15–18 °C/100 MPa) and considered as the primary cause for temperature rise. The temperature rise due to heat of compression is reversible upon depressurization, while the temperature rise due to dissipation of kinetic energy during homogenization is irreversible (Martínez‐Monteagudo et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As compared to heat of compression (3 °C/100 MPa for water at 25 °C initial temperature), the heat generated during homogenization is much higher (15–18 °C/100 MPa) and considered as the primary cause for temperature rise. The temperature rise due to heat of compression is reversible upon depressurization, while the temperature rise due to dissipation of kinetic energy during homogenization is irreversible (Martínez‐Monteagudo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Premixed products (see section 2.1) were loaded into the sample reservoir at 21 °C, and homogenized at 25, 50, 75, and 100 MPa for a single pass. Based on our earlier research (Martínez‐Monteagudo et al, ), it was observed that modest homogenization pressure (100 MPa) helped to preserve product quality and physical stability, and reduce stabilizer concentration in certain dairy beverages. Thus, the pressure range of 25–100 MPa was used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical characteristics and emulsion stability of nutritional formulations were evaluated on a pilot-scale HPH unit [11]. The authors reported that homogenization at pressures from 100-150 MPa yielded more shear-thinning fluids with increased physical stability, representing an opportunity to reduce the concentration of stabilizers in dairy beverages.…”
Section: Introductionmentioning
confidence: 99%
“…Olson, White, and Watson () showed changes in the meltdown rate of reduced fat ice cream produced from microfluidized milk, but Cavender and Kerr () did not see similar effects in full fat ice creams. More recent work has shown that high‐pressure homogenization can reduce stabilizer use rates (Martínez‐Monteagudo et al, ) and improve physical stability (Rodarte, Zamora, Trujillo, & Juan, ) of dairy products.…”
Section: Introductionmentioning
confidence: 99%